Corn silk polysaccharides attenuate diabetic nephropathy through restoration of the gut microbial ecosystem and metabolic homeostasis - Dong, Wenting; Zhao, Yuanyuan; Li, Xiuwei; Huo, Jinhai; Wang, Weiming (Frontiers in Endocrinology, 2023)
The pathogenesis of diabetic nephropathy (DN) is complex, inflammation is the central link among the inducing factors in the existing research, and the gut-kidney axis could scientifically explain the reasons for the accumulation of chronic low-grade inflammation. As both a medicine and food, corn silk contains abundant polysaccharides. Historical studies and modern research have both confirmed its intervention effect on diabetes and DN, but the mechanism of action is unclear. In this study, a DN rat model was generated, and the therapeutic effect of corn silk polysaccharides (CSPs) was evaluated based on behavioral, histopathological and biochemical indicators. We attempted to fully understand the interactions between CSPs, the gut microbiota and the host at the systemic level from a gut microbiota